RADpainter and fineRADstructure: Population Inference from RADseq Data. (20th February 2018) - Malinsky, Milan; Trucchi, Emiliano; Lawson, Daniel John; Falush, Daniel
Abstract: Powerful approaches to inferring recent or current population structure based on nearest neighbor haplotype "coancestry" have so far been inaccessible to users without high quality genome-wide haplotype data. With a boom in nonmodel organism genomics, there is a pressing need to bring these methods to communities without access to such data. Here, we present RADpainter, a new program designed to infer the coancestry matrix from restriction-site-associated DNA sequencing (RADseq) data. We combine this program together with a previously published MCMC clustering algorithm into fineRADstructure —a complete, easy to use, and fast population inference package for RADseq data (https://github.com/millanek/fineRADstructure ; last accessed February 24, 2018). Finally, with two example data sets, we illustrate its use, benefits, and robustness to missing RAD alleles in double digest RAD sequencing.